(untitled) - Thielen, David (New York, 1999)
Concise and to-the-point, David Thielen's insider's report on how Microsoft achieved the impossible - retaining the responsiveness of a small company as it became one of the largest corporations in the world - is a primer on what any company must do to reach the top. Painting a compelling portrait of Microsoft's culture, this ready-to-use book encompasses the core principles that propel every Microsoft employee to excel and direct every manager's thought process. Turn to any page and you will find valuable practices and insights that can be applied to your own company. Imagine how following these Microsoft standards could instantly increase your firm's productivity: Immediately after each project is completed, a ruthless "post-mortem" process ignores the project's successes to dissect its ailures...and how they can be avoided in the future; Instead of wallowing in profit-induced security, Microsoft immediately begins to develop replacements for its cash-cow products - knowing that if they don't, the competition will; Smaller is not just better, it is essential, but work groups, while functionally independent, still pursue a common strategic plan; Could your company survive outside the 9-to-5 ritual? Find examples of how Microsoft's focus on task completion instead of time clocks leads to unmatched employee morale and superior effort.
Keywords: Quản trị công nghiệp,Industrial management